Hey guys,

Why is it that the answer to -2^4 and (-2)^4 is different, but the answer to -2^3 and (-2)^3 is the same?

At first, I thought it had something to do with one side being raised to an even number and the other to an odd number.

If that were the case, both sides should have the same answer.

So, I went riffling through my notes and remembered that if the sign is outside parenthesis, it is not considered part of the base.

So I tried it out:

-2^4 = -1 x -2 x -2 x -2 x -2 = -16

(-2)^4 = (-2)(-2)(-2)(-2) = 16

But if I apply the same rule to the other side, it gives me two different answers:

-2^3 = -1 x -2 x -2 x -2 = 8

(-2)^3 = (-2)(-2)(-2) = -8

I am so confused! am I doing something wrong here?

## Bookmarks